Demand for food and nutrients and its climate impact: A micro-econometric analysis of economic and socio-demographic drivers - Irz, Xavier (Natural Resources Institute Finland, Luke, 2017)
Demand for food in Finland has changed dramatically in recent decades and is continuously evolving as the result of multiple influences, including the relative prices of food items, economic growth, short-term variations in purchasing power, demographic changes, food scares, and other changes in preferences linked to nutrition, animal welfare, and environmental issues. Yet, little is known about the relative importance of those factors in shaping food demand, which appears problematic for both public policy makers and the private stakeholders of the food chain. For instance, it is becoming clear that transition to a low-carbon economy will require adjusments in consumption patterns, given the limited possibilities of mitigation through modification of production patterns and technology, but much debate remains about how to make that change happen. Similarly, the aging population and the growing number of single-person households have implications for the evolution of Finnish food consumption that remain, as yet, poorly understood by the stakeholders of the food chain. Thus, we present a fresh analysis of Finnish food consumption based on the econometric estimation of a complete system of demand for food. The data originates from the 2012 Finnish Household Budget Survey, which contains over 3550 observations and gives a detailed account of household food consumption over a two-week period for more than 200 food categories. Those are aggregated into 19 product categories, hence ensuring the empirical tractability of the behavioural model, which is then linked to technical coefficients describing the nutritional properties and climate impact of each food aggregate. The demand system uses the recently developed Exact Affine Stone Index (EASI) functional form, which offers great flexibility in relating consumption to income and can therefore accommodate the highly non-linear Engel curves typically found in micro-level data. Estimation tackles two issues caused by the nature of the data, namely censored demand due to the high number of zero-consumption observations attributable to the short period of data collection, and the adjustment of unit values to measure prices. The results are presented in terms of elasticities summarizing the responses of food and nutrient demands as well as greenhouse gas emissions to changes in economic and socio-demographic variables. In future work, those elasticities will support the analysis of policies aimed at increasing the sustainability of food consumption patterns in Finland. In particular, the estimated models can be utilised to simulate the effects of fiscal measures (e.g., a carbon tax) as well as dietary recommendations on diet quality, health, the climate, and economic welfare. Elintarvikkeiden kysyntä on muuttunut Suomessa dramaattisesti viime vuosikymmeninä, ja se kehittyy jatkuvasti useiden tekijöiden vaikutuksesta. Näitä tekijöitä ovat mm. eri elintarvikkeiden suhteelliset hinnat, talouskasvu ja ostovoiman kehitys, väestörakenteen muutokset, elintarvikekohut sekä kuluttajien muuttuva suhtautuminen ravitsemukseen, eläinten hyvinvointiin ja ympäristöasioihin. Silti varsin vähän tiedetään siitä, kuinka tärkeitä nämä tekijät suhteellisesti ottaen ovat elintarvikekysynnän muovaamisessa. Tämä on ongelmallista sekä päätöksentekijöille että alan sidosryhmille. On esimerkiksi käymässä selväksi, että vähähiiliseen talouteen siirtyminen tulee vaatimaan muutoksia kulutustottumuksissa, kun huomioidaan tuotantoteknologian rajalliset mahdollisuudet. On kuitenkin edelleen epäselvää, kuinka tällainen muutos saadaan aikaan. Myös väestön vanheneminen ja yhden hengen kotitalouksien määrän kasvu muuttavat elintarvikkeiden kulutusta tavalla, jota elintarvikeketjun sidosryhmät eivät toistaiseksi kunnolla ymmärrä. Tässä tutkimuksessa esitetään sen vuoksi ekonometriseen estimointiin perustuva analyysi suomalaisen elintarvikekulutuksesta ja siihen vaikuttavista tekijöistä. Tietoaineisto on peräisin Tilastokeskuksen vuoden 2012 kulutustutkimuksesta, joka sisältää yli 3 550 havaintoa ja antaa yksityiskohtaisen kuvauksen kotitalouksien elintarvikekulutuksesta kahden viikon ajalta yli 200 elintarvikkeesta. Elintarvikkeet on aggregoitu 19 eri tuoteryhmään, mikä varmistaa estimoidun kysyntämallin empiirisen jäljitettävyyden. Malliin on liitetty teknisiä kertoimia, jotka kuvaavat kunkin tuoteryhmän ravin-toarvoa ja ilmastovaikutusta. Kysyntäjärjestelmä hyödyntää äskettäin kehitettyä Exact Affine Stone Index funktiomallia (EASI), jolla kulutus voidaan suhteuttaa hyvin joustavasti tulotason kehitykseen siten, että analyysiin saadaan mukaan myös mikrotason aineistoissa tyypillisesti esiintyvät erittäin epälineaariset Engelin käyrät. Tämä ratkaisee kaksi tietoaineiston luonteesta johtuvaa ongelmaa, joita ovat ns. piiloon jäävä kysyntä, joka johtuu lyhyen aineistonkeräysjakson synnyttämistä runsaista nollahavainnoista, sekä yksikköarvojen korjaukset hintojen mittaukseen. Tulokset esitetään joustoina, jotka kertovat taloudellisissa ja sosiodemografisissa tekijöissä tapahtuvien muutosten vaikutukset elintarvike- ja ravintoainekysyntään sekä kasvihuonekaasupäästöihin. Estimoituja joustoja voidaan hyödyntää jatkossa arvioitaessa esimerkiksi ruoan kulutustottumusten kestävyyden lisäämiseen tähtäävien poliittisten toimenpiteiden vaikuttavuutta. Estimoiduilla kysyntämalleilla voidaan simuloida esimerkiksi veropoliittisten toimenpiteiden (esim. hiilivero) sekä ruokavaliosuositusten vaikutusta ruokavalion laatuun, terveyteen, ilmastoon ja taloudelliseen hyvinvointiin.
Keywords: food; food demand; EASI; elintarvikkeet; ruokavaliot; diet; elasticity; demand; kysyntä